Unconditional Cash Transfer Policy as an Effort to Prevent Stunting: A Study On Jember, East Java - Putra, Allen Pranata; Astuti, Sri Juni Woro; Ibrahim, Kabiru Hannafi (UI Scholars Hub, 2024)
This study evaluates the impact of the Unconditional Cash Transfer (UCT) policy in preventing stunting in Jember, East Java. Stunting, a result of chronic malnutrition, remains a significant public health challenge in Indonesia, with Jember exhibiting higher prevalence rates than the national average. The UCT policy aims to improve the welfare of low-income families by providing direct financial assistance, allowing them to meet basic needs, including nutrition. This research utilizes a qualitative approach through case studies and interviews with relevant stakeholders to assess the effectiveness of UCT in enhancing children's nutrition and health. The findings indicate that while UCT has a positive short-term impact on improving family income and child nutrition, challenges persist regarding the sustainability of these outcomes post-assistance. The study highlights the necessity for integrating UCT with nutrition education and access to quality health services to ensure long-term benefits. These results suggest that a holistic approach, combining financial aid with educational interventions, is crucial for effective stunting prevention. The implications of this study extend to policymakers, emphasizing the importance of a multifaceted strategy for combating malnutrition and fostering sustainable development.